Airway management for anaesthesia in the ambulatory setting. Issue 6 (December 2015) - Hinkelbein, Jochen; Hohn, Andreas; Genzwürker, Harald
Abstract : Purpose of review: The number of anaesthetic procedures in the ambulatory setting is steadily increasing. During the last years, more and more patients with complex medical conditions undergo ambulatory interventions. This review will focus on airway management practices, but especially on techniques used in the ambulatory setting. It will highlight recent literature published in the focus of ambulatory anaesthesia and will discuss relevant findings of the last year. Methods: Literature search and analysis performed independently by two reviewers. Recent findings: Practical points to improve success of anaesthesia and to avoid complications in the ambulatory setting are provided. In addition to concepts for the (un)expected difficult airway, new supraglottic devices, and modern concepts for teleconsultation, are discussed. Summary: There are several points which should be considered for ambulatory anaesthesia. Selected patient groups (e.g., obstructive sleep apnoea, obesity) may have a higher anaesthesia-related risk. To handle the more and more complex conditions in a growing number of ambulatory patients, straightforward concepts, especially for the (un)expected difficult airway, are required.